Enhancing medical communication skills through video-recorded peer role-play and a standardized checklist - Pallavi L.C; Chinmay Suryavanshi; Krishnamoorthi Prabhu; Archana Chauhan; Kirtana Raghurama Nayak; Ramnarayan Komattil (PLoS ONE, 2026)
Objective Developing communication skills early during medical training requires structured opportunities for practice, observation, and reflection. This study integrated video-recorded peer role-play with a standardized checklist to foster communication skill competencies among first-year medical students. Methods A communication skills module was designed for 250 first-year MBBS students as part of the Attitude EThics COMmunication (AETCOM) course. The intervention integrated video-based submission of peer role-play of doctor‒patient interviews guided by a standardized, culturally contextualized checklist (Observation-Based Communication Skills Checklist; OCSC). The entire module was managed through the institutional learning management system (LMS). Student perceptions were gathered via a validated questionnaire and two focus group discussions (FGDs). Results Of 241 valid submissions, 70% met expectations, and 28% exceeded them. Student feedback was overwhelmingly positive, with 87% agreeing that peer role-play was an effective learning method. A majority (91%) reported that the OCSC-guided video assignment provided a structured and reflective learning experience. Thematic analysis of FGDs revealed that checklist-guided role-play was helpful for skill acquisition, video assignment consolidated learning, and faculty feedback was crucial for improvement. Conclusion The integration of video-recorded peer role-play, a standardized checklist, and an LMS provides a scalable and effective framework for teaching, assessing, and reinforcing foundational communication skills in early-phase medical learners.